Prosthodontic Rehabilitation of a Patient with Mal-aligned Teeth: A Conservative Esthetic Approach - Neelam Pande; Krutika Borle; Pawan Rathod; Saee Deshpande; Apeksha Patil (International Journal For Multidisciplinary Research, 2026)
Esthetic rehabilitation of patients presenting with mal-aligned dentition and mutilated anterior teeth poses a significant clinical challenge, requiring a comprehensive and conservative treatment approach. Such cases demand careful evaluation of functional, biological, and esthetic parameters to achieve optimal outcomes